Alterations of Functional Connectivity in Stroke Patients With Basal Ganglia Damage and Cognitive Impairment - Yao, Guanqun; Li, Jing; Liu, Sha; Wang, Jiaojian; Cao, Xiaohua; Li, Xinrong; Cheng, Long; Chen, Huafu; Xu, Yong (Frontiers in Neurology, 2020)
Stroke with basal ganglia damage (SBG) is a neurological disorder characterized by cognitive impairment. The neurobiological mechanism of cognitive impairment in stroke patients with basal ganglia damage (SBG-patients) remain unclear. This study is aimed to explore the underlying neurobiological mechanism of cognitive impairment in SBG-patients by using resting-state functional magnetic resonance imaging (rsfMRI).The alterations of functional connectivity (FC) between 14 SBG-patients (the average ages: 61.00±7.45 years) and 21 healthy controls (HC) (the average ages: 60.67±6.95 years) were examined using voxel-mirrored homotopic connectivity (VMHC) and degree centrality (DC). Moreover, we compared the subjects' cognitive function by utilizing the Chinese Revised Wechsler Adult Intelligence Scale (WAIS-RC) and Wechsler Memory Scale (WMS).The full scale of intelligence quotient (FIQ) (t=2.810, p<0.010) and Memory Quotient (MQ) (t=2.920, p<0.010) scores of SBG-patients were obviously lower than the scores of HC. At the same time, compared with HC, significantly decreased VMHC values in the bilateral angular gyrus, supramarginal gyrus, inferior frontal gyrus, middle temporal gyrus, hippocampus, precuneus, precentral gyrus and middle occipital gyrus, and decreased DC values in the right supramarginal gyrus, bilateral angular gyrus and right postcentral central gyrus were observed in SBG-patients. Moreover, the VMHC values in the angular gyrus, inferior frontal gyrus, supramarginal gyrus, middle temporal gyrus and the DC values in the right supramarginal gyrus were significantly correlated with cognitive functions in all participants.The study may provide a basis for cognitive impairment in SBG-patients. Furthermore, local abnormalities and interhemispheric interaction deficits may be the key characteristics in the potential physiological mechanism of cognitive impairment in SBG-patients, which provides new ideas and insights to understand and treat SBGpatients' cognitive impairment in the future.